Meditative Silence and Reciprocity: The Dialogic Implications for "Spiritual Sites of Composing" - George Kalamaras (Journal of the Assembly for Expanded Perspectives on Learning, 1996)
Recent studies of silence must focus on the dialogical nature of Eastern meditation, examining the values of meditative awareness and social theories of reciprocity.